Perceived Competition And Management Control Systems Attributes Of Companies In Malaysia - Foong , Soon Yau (Asian Academy of Management (AAM), 2001)
Competition in the market place is increasingly becoming more intense with globalisation. The role of management control system to monitor the effectiveness of competitive strategy and to provide feedback for adjustment to strategy has become more important. This study examines the perceived intensity of five bases of competition and the competitive priorities or orientations of 93 firms located in the Klang Valley. The attributes of management control systems of these organizations in relation to their competitive priorities and perceived competition were also examined. A structured questionnaire was used. The results show that the participating organizations were still stressing on competition based on price, quality and service, with lower emphasis on competition based on product innovation and variety. Organizations with high-index of perceived competition had significantly more extensive and frequent use of accounting-based controls and top-down form of communication than those organizations with low-index of perceived competition. The limitations of the study and implications of the findings are discussed.